How economists model the world into numbers - Boumans, Marcel (Routledge, 2005)
This book provides a critical analysis of the economist's favourite tool, and as such will be an enlightening read for some, and an intriguing one for others.
Keywords: Economics, Mathematical.; Economics -- Mathematical models.; Econometrics.; Economics -- Methodology -- History -- 20th century.; Economics, Mathematical -- History -- 20th century.; Économie politique -- Modèles mathématiques.; Économétrie.; Économie politique -- Méthodologie -- Histoire -- 20e siècle.; Mathématiques économiques.; Mathématiques économiques -- Histoire -- 20e siècle.; BUSINESS & ECONOMICS -- Econometrics.; BUSINESS & ECONOMICS -- Statistics.; Econometrics; Economics, Mathematical; Economics -- Mathematical models; Economics -- Methodology; 1900-1999; History